Early Tibial Component Fractures in a Cementless, 3D-Printed, Titanium Implant - Alan D. Lam, BS; Gavan P. Duffy, MD (Arthroplasty Today, 2022)
Fracture of the tibial baseplate in total knee arthroplasty is a rare occurrence, particularly in short- and mid-term follow-up. This case series documents the first known report in the literature of fatigue fracture of a cementless, 3D-printed, highly porous titanium tibial component. We recommend regular follow-up visits with radiographs to confirm adequate total knee arthroplasty component positioning and alignment.